HUBUNGAN TINGKAT PENGETAHUAN TINGKAT PENDIDIKAN DAN JENIS PEKERJAAN IBU DENGAN STATUS IMUNISASI BAYI USIA 9 SAMPAI 12 BULAN - Amalia, Rizki; Rahmadhani, Sendy Pratiwi; Sari, Lely Meriaya (JOURNAL OF MIDWIFERY SCIENCE, 2021)
Background: Immunization is an effort to provide immunity to infants and children by introducing vaccines into the body so that the body makes antibodies to prevent certain diseases. Objective: To determine the relationship between the level of knowledge, education level, and type of work of the mother with the basic immunization status of infants aged 9 to 12 months. Methods: This research is quantitative by using a cross sectional research design. The population of this study were all mothers who had babies aged 9-12 months. The research sample is part of the population that meets the criteria to become respondents. The sampling technique used in this research is purposive sampling. Data analysis used univariate analysis and bivariate analysis. Results: Based on the results of the chi-square statistical test with a significance level of = 0.05, knowledge obtained p value = 0.033, education level obtained p value = 0.023, occupation obtained p value = 0.004 which means that there is a relationship between knowledge, education, mother's occupation and completeness of immunization. basic baby age 9-12 months. Conclusion: There is a relationship between the level of knowledge, education level, and type of work of the mother with the status of the mother Key words: Knowledge, education level, type of mother's occupation, basic immunization imunisasi